2020
DOI: 10.1083/jcb.202003041
|View full text |Cite
|
Sign up to set email alerts
|

G1/S transcription factors assemble in increasing numbers of discrete clusters through G1 phase

Abstract: In budding yeast, the transcription factors SBF and MBF activate a large program of gene expression in late G1 phase that underlies commitment to cell division, termed Start. SBF/MBF are limiting with respect to target promoters in small G1 phase cells and accumulate as cells grow, raising the questions of how SBF/MBF are dynamically distributed across the G1/S regulon and how this impacts the Start transition. Super-resolution Photo-Activatable Localization Microscopy (PALM) mapping of the static positions of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
2
9
0
Order By: Relevance
“…We carried out a similar analysis for Whi5 and found that Whi5 concentration decreased by approximately 30% in rich carbon and 20% in poor carbon, consistent with the fact that Whi5 protein levels do not change substantially and there is only a small increase in cell size in G1 phase ( Figure 1—figure supplement 1F ). Our results are consistent with several previous studies that observed a relatively small increase in cell volume in G1 phase ( Ferrezuelo et al, 2012 ; Leitao and Kellogg, 2017 ) and little or no change in Whi5 concentration ( Dorsey et al, 2018 ; Litsios et al, 2019 ; Black et al, 2020 ). A previous study found that a small fraction of cells growing in complete synthetic media containing poor carbon show a 30–40% decrease in Whi5 concentration, but most cells showed a decrease of 20–30% or less ( Schmoller et al, 2015 ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…We carried out a similar analysis for Whi5 and found that Whi5 concentration decreased by approximately 30% in rich carbon and 20% in poor carbon, consistent with the fact that Whi5 protein levels do not change substantially and there is only a small increase in cell size in G1 phase ( Figure 1—figure supplement 1F ). Our results are consistent with several previous studies that observed a relatively small increase in cell volume in G1 phase ( Ferrezuelo et al, 2012 ; Leitao and Kellogg, 2017 ) and little or no change in Whi5 concentration ( Dorsey et al, 2018 ; Litsios et al, 2019 ; Black et al, 2020 ). A previous study found that a small fraction of cells growing in complete synthetic media containing poor carbon show a 30–40% decrease in Whi5 concentration, but most cells showed a decrease of 20–30% or less ( Schmoller et al, 2015 ).…”
Section: Resultssupporting
confidence: 93%
“…We used the same approach to calculate the fold change in Whi5 levels between the zero time point and bud emergence in multiple biological replicates ( Figure 1—figure supplement 1D ). Both plots suggest that levels of the Whi5 protein do not change substantially before bud emergence in rich or poor carbon, consistent with several previous studies that used microscopy to analyze fluorescently tagged versions of Whi5 ( Schmoller et al, 2015 ; Dorsey et al, 2018 ; Litsios et al, 2019 ; Black et al, 2020 ).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…A third parameter quantified in cell differentiation besides TF bound-fraction ( figure 2 ) and residence time ( figure 3 ) was accumulation of SRF molecules in clusters by TALM ( figure 5 ). Others have already used TALM protocols for membrane and mitochondrial proteins [ 33 , 45 , 46 ] as well as nuclear proteins [ 65 , 66 ]. In the nucleus, previous studies argued that such TF aggregates or clusters might indicate presence of so-called transcriptional hot-spots or hubs where specific gene clusters are predominantly transcribed [ 7 , 43 ].…”
Section: Discussionmentioning
confidence: 99%